Impact of different shade coffee management scenarios, on a population of Oncidium poikilostalix (Orchidaceae), in Soconusco, Chiapas, Mexico. (4th May 2017) - García-González, Alfredo; Damon, Anne; Raventós, José; Riverón-Giró, Frander B.; Mújica, Ernesto; Solís-Montero, Lislie
Abstract : Background : Understanding the effect of perturbation, be it natural or anthropogenic, on the demography and dynamics of the plant populations can help conservation management planning. Aims : We assessed the impacts of management of a shade coffee plantation on a population of Oncidium poikilostalix (Orchidaceae). Methods : We studied in a coffee ( Coffea arabica ) agroecosystem the impact of the current traditional management [T] and two hypothetical epiphyte control management scenarios (intense 'desmusgue' [ID] and moderate 'desmusgue' [MD]), on the only known Mexican population of O . poikilostalix . Based on 3 years of field demographics data, the population dynamics of the orchid were projected using T, ID and MD scenarios for 20 years into the future. Results : Under the current management T, the population of O. poikilostalix was projected to grow continuously (λ = 1.102). Conversely, under management ID, the loss of individuals would lead to a sustained population decline (λ = 0.843); in the case of MD, the population would decline more slowly with the population growth rate tending towards equilibrium (λ = 0.966). Conclusions : The changes in the management of coffee plantations that have become common throughout the south-east of Mexico represent a threat to the survival of the only population of O. poikilostalix in Mexico, and likely threaten other epiphytic species.